2016
DOI: 10.1088/1367-2630/18/1/013048
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic quantum Zeno by large deviation theory

Abstract: Quantum measurements are crucial for observing the properties of a quantum system, which, however, unavoidably perturb its state and dynamics in an irreversible way. Here we study the dynamics of a quantum system being subjected to a sequence of projective measurements applied at random times. In the case of independent and identically distributed intervals of time between consecutive measurements, we analytically demonstrate that the survival probability of the system to remain in the projected state assumes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 43 publications
3
75
0
Order By: Relevance
“…Then, since the discrepancy between the statistical averages, here investigated, do strongly depend on the second and fourth statistical moments of the noise distribution m ( ) p outside the Zeno regime, one could effectively determine the influence of the stochastic noise source on the dynamics of a fully controlled quantum system, hence characterising the external environment. On top of that, although we have explicitly studied Hamiltonian dynamics and applied the projective measurement on an initial pure state, the method can be also generalised to arbitrary mixed input states with the dynamics being described by completely positive trace-preserving maps [30] and to the case of measurements projecting the system on higher dimensional Hilbert subspaces, hence leading to Stochastic Quantum Zeno Dynamics [25,26,32]. Finally, these results are expected to represent further steps towards controlled manipulations of quantum systems via dissipative interactions [33,34] where one can indeed control the noisy environment or part of it in order to perform desired challenging tasks like the ones necessary for future quantum technologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, since the discrepancy between the statistical averages, here investigated, do strongly depend on the second and fourth statistical moments of the noise distribution m ( ) p outside the Zeno regime, one could effectively determine the influence of the stochastic noise source on the dynamics of a fully controlled quantum system, hence characterising the external environment. On top of that, although we have explicitly studied Hamiltonian dynamics and applied the projective measurement on an initial pure state, the method can be also generalised to arbitrary mixed input states with the dynamics being described by completely positive trace-preserving maps [30] and to the case of measurements projecting the system on higher dimensional Hilbert subspaces, hence leading to Stochastic Quantum Zeno Dynamics [25,26,32]. Finally, these results are expected to represent further steps towards controlled manipulations of quantum systems via dissipative interactions [33,34] where one can indeed control the noisy environment or part of it in order to perform desired challenging tasks like the ones necessary for future quantum technologies.…”
Section: Discussionmentioning
confidence: 99%
“…In [26], it has been proved that this most probable value is equivalent to the log-average of the quantity m ( ) q with respect to m ( ) p , namely to the geometric average  g of the survival probability weighted by m ( ) p :…”
Section: Theorymentioning
confidence: 99%
“…An important observation is that the bounds on fluctuations of a counting observable and its FPTs are controlled by the average dynamical activity, in analogy to the role played by the entropy production in the case of currents [1,13]. We hope these results will add to the growing body of work applying large deviation ideas and methods to the study of dynamics in driven systems [29][30][31][32][33][34][35][36][37][38][39][40][41], glasses [25,[42][43][44][45][46][47], protein folding and signaling networks [48][49][50][51], open quantum systems [52][53][54][55][56][57][58][59][60][61][62][63][64], and many other problems in nonequilibrium [65][66][67][68][69][70][71][72].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, sequences of Zeno measurements have been studied in the presence of additional stochastic contributions to analyze how the confinement probability of the system to remain in the measured subspace changes with the amount and type of stochasticity [36][37][38]. Such a regime is called weak quantum Zeno (WQZ) and it has been observed that, although projective measurements could constantly monitor a quantum system, its decay is boosted by the presence of disorder.…”
Section: Introductionmentioning
confidence: 99%